(untitled) (LEARNing Landscapes, 2009)
This study is part of a larger inquiry (Clandinin & Connelly, 2000), attended to children’s, teachers’, and parents’ narratives of experience situated within institutional, cultural, and social narratives shaping particular school contexts. As one teacher engaged in an autobiographical narrative inquiry alongside her mother’s lived and told stories, she learned curriculum making is intergenerational and woven with identity making. This teacher’s narrative inquiry led her to new ways of knowing, reshaping her practice. The study illuminates the importance of attending to the interwoven, intergenerational stories of teachers, children and parents stories in co-composing a curriculum of lives.